Induction of food-specific IgG by Gene Gun-delivered DNA vaccines - Smeekens, Johanna M.; Kesselring, Janelle R.; Frizzell, Hannah; Bagley, Kenneth C.; Kulis, Michael D. (Frontiers in Allergy, 2022)
Background Shellfish and tree nut allergies are among the most prevalent food allergies, now affecting 2%–3% and 1% of the US population, respectively. Currently, there are no approved therapies for shellfish or tree nut allergies, with strict avoidance being the standard of care. However, oral immunotherapy for peanut allergy and subcutaneous immunotherapy for environmental allergens are efficacious and lead to the production of allergen-specific IgG, which causes suppression of allergen effector cell degranulation. Since allergen-specific IgG is a desired response to alleviate IgE-mediated allergies, we tested transcutaneously-delivered DNA vaccines targeting shellfish and tree nut allergens for their ability to induce antigen-specific IgG, which would have therapeutic potential for food allergies. Methods We assessed Gene Gun-delivered DNA vaccines targeting either crustacean shellfish or walnut/pecan allergens, with or without IL-12, in naïve mice. Three strains of mice, BALB/cJ, C3H/HeJ and CC027/GeniUnc, were evaluated for IgG production following vaccination. Vaccines were administered twice via Gene Gun, three weeks apart and then blood was collected three weeks following the final vaccination. Results Vaccination with shellfish allergen DNA led to increased shrimp-specific IgG in all three strains, with the highest production in C3H/HeJ from the vaccine alone, whereas the vaccine with IL-12 led to the highest IgG production in BALB/cJ and CC027/GeniUnc mice. Similar IgG production was also induced against lobster and crab allergens. For walnut/pecan vaccines, BALB/cJ and C3H/HeJ mice produced significantly higher walnut- and pecan-specific IgG with the vaccine alone compared to the vaccine with IL-12, while the CC027 mice made significantly higher IgG with the addition of IL-12. Notably, intramuscular administration of the vaccines did not lead to increased antigen-specific IgG production, indicating that Gene Gun administration is a superior delivery modality. Conclusions Overall, these data demonstrate the utility of DNA vaccines against two lifelong food allergies, shellfish and tree nuts, suggesting their potential as a food allergy therapy in the future.